Peran Orang Tua Dalam Mengenalkan Huruf Hijaiyah Pada Anak Usia Dini Di Gampong Meunasah Dayah Kecamatan Muara Satu Kota Lhokseumawe - Rahmah, Syarifah (LP. Ma'arif Janggan Magetan, 2023)
This research was conducted to examine the Role of Parents in Introducing Hijaiyah Letters to Early Childhood, the method used was qualitative research with observation, interview and documentation techniques. The results of the study are that in introducing hijaiyah letters to early childhood in Gampong Meunasah Dayah, parents play the role of: 1) The teacher is in charge of introducing hijaiyah letters to children, guiding children to read hijaiyah letters, getting used to and training children to read Juz-Amma (hijaiyah letters ). 2) Parents act as motivators whose job is to motivate children, while the way parents motivate children to want to read hijaiyah letters is by giving advice, giving affection, taking children to TPA and also giving gifts to children if the children are diligent read Juz-Amma. 3) Parents as supervisors who always follow the development of children's achievements and supervise children both at home, school or at TPA.